RELATIONSHIP BETWEEN ENTREPRENEURIAL MINDSET AND JOB CREATION AMONG BUSINESS EDUCATION GRADUATES (NAU Journal of Technology and Vocational Education, 2025)
The study examined entrepreneurial mindset and job creation among business education graduates. Two research questions guided the study. A descriptive research design of survey was used. The population comprised Business Education postgraduate students in Olabisi Onabanjo University, Ago-Iwoye and Tai Solarin University of Education, Ijagun, Ogun State. A total of 100 Business Education postgraduate students of Olabisi Onabanjo University, Ago-Iwoye and Tai Solarin University of Education were selected as sample size of the study. Purposive and stratified sampling techniques were used for selecting the sample size. The study used researcher self-developed instrument tagged: Entrepreneurial Mindset and Job Creation Questionnaire (EMJCQ) with (r = .94 as reliability coefficient. Research questions 1 and 2 were answered using descriptive statistics of mean and standard deviation as well as PPMC. The findings of the study indicated that confident about self-business abilities, motivation to own a business venture, mindset to expands business, starting own business, innovative business was among the significance of entrepreneurial mindset on job creation among business education graduates. Entrepreneurial mindset positively related with job creation among business education graduates. The implications of this result were that Business education graduates with high entrepreneurial mindset supposed to work for self and become employer of labour. Government through university efforts should trained their students on how to develop entrepreneurial mindset through effective teaching and learning of entrepreneurship education.
Keywords: Entrepreneurial mindset; job creation; business education graduates